Factors Affecting the Development of Small Medium Enterprises in the Niger Republic: An Exploratory Study - Hamidou Taffa Abdoul-Azize (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Over the past few years, the Republic of Niger has seen an increase in young entrepreneurs across a wide range of sectors. Many obstacles could impede the progress of these entrepreneurs. This study examines the factors that affect the development of small-medium enterprises in the Niger Republic. Based on primary data collected from entrepreneurs, factor analysis was performed. The findings of the study showed that the most significant factors of the development of small-medium enterprises in the Niger Republic were the "internal structure of the enterprise, followed by the characteristics of the entrepreneurs, and lastly the external environment of the enterprise. Finally, the study concludes with some recommendations for policymakers and educational institutions to promote the productivity of the small-medium enterprises and to stimulate entrepreneurial enthusiasm among youth that could enhance the country's economy.